ATP Facilitates Staphylococcal Enterotoxin O Induced Neutrophil IL-1β Secretion via NLRP3 Inflammasome Dependent Pathways - Hou, Fengqing; Peng, Lianci; Jiang, Jiali; Chen, Tingting; Xu, Dongyi; Huang, Qingyuan; Ye, Chao; Peng, Yuanyi; Hu, Dong-Liang; Fang, Rendong (Frontiers in Immunology, 2021)
Staphylococcus aureus (S. aureus) is an important zoonotic food-borne pathogen causing severe invasive infections, such as sepsis, pneumonia, food poisoning, toxic shock syndrome and autoimmune diseases. Staphylococcal enterotoxin O (SEO) is a new type of enterotoxins of S. aureus with superantigenic and emetic activity. However, it is still unclear about SEO-induced host inflammatory response. Therefore, the mechanism of SEO-induced interleukin-1β (IL-1β) secretion in mouse neutrophils was investigated in this study. Our results showed that recombinant SEO had superantigenic activity with high level of gamma interferon (INF-γ) production in mouse spleen cells and induced inflammatory cytokines expression including IL-1α, IL-1β, IL-6 and TNF-α in neutrophils under the action of ATP. In addition, SEO-induced IL-1β secretion was dependent on activation of Toll like receptor 4 (TLR4), nuclear factor kappa B (NF-κB) and c-jun N-terminal kinase (JNK) signaling pathways. However, SEO-induced IL-1β secretion was abolished in the neutrophils of NLRP3-/- mice compared with those of wild type mice, indicating that activation of NLRP3 inflammasome mediated IL-1β secretion during neutrophils stimulation with SEO under the action of ATP. Moreover, this process of SEO+ATP-induced IL-1β secretion was dependent on potassium (K+) efflux. Taken together, our study suggests that activation of TLR4/JNK/NLRP3 inflammasome signaling pathway mediate maturation and secretion of IL-1β and provides a new insight on S. aureus virulence factor-induced host immune response.